A gene cluster for taurine sulfur assimilation in an anaerobic human gut bacterium. Issue 15 (15th August 2019) - Xing, Meining; Wei, Yifeng; Hua, Gaoqun; Li, Mengya; Nanjaraj Urs, Ankanahalli N.; Wang, Feifei; Hu, Yiling; Zhai, Weixiang; Liu, Yangping; Ang, Ee Lui; Zhao, Huimin; Zhang, Yan
Abstract : Aminoethylsulfonate (taurine) is widespread in the environment and highly abundant in the human body. Taurine and other aliphatic sulfonates serve as sulfur sources for diverse aerobic bacteria, which carry out cleavage of the inert sulfonate C–S bond through various O2 -dependent mechanisms. Taurine also serves as a sulfur source for certain strict anaerobic fermenting bacteria. However, the mechanism of C–S cleavage by these bacteria has long been a mystery. Here we report the biochemical characterization of an anaerobic pathway for taurine sulfur assimilation in a strain of Clostridium butyricum from the human gut. In this pathway, taurine is first converted to hydroxyethylsulfonate (isethionate), followed by C–S cleavage by the O2 -sensitive isethionate sulfo-lyase IseG, recently identified in sulfate- and sulfite-reducing bacteria. Homologs of the enzymes described in this study have a sporadic distribution in diverse strict and facultative anaerobic bacteria, from both the environment and the taurine-rich human gut, and may enable sulfonate sulfur acquisition in certain nutrient limiting conditions.